Optical antenna of comb-shaped split ring architecture for increased field localization in NIR and MIR - Erturk, Vakur B. (2014)
We propose and demonstrate novel designs of optical antennas based on comb-shaped split ring architecture that display multi resonance field intensity enhancement spectrum. These nanoantennas achieve substantially increased field localization at longer wavelengths than that of a single or an array of dipoles with the same side length. With these optical antennas, localizing near infrared (NIR) and mid infrared (MIR) lights within a region of tens of nanometers at an intensity enhancement level of the order of thousands of magnitude can be accomplished.